Do German welfare-to-work programmes reduce welfare and increase work? - Martin Huber; Michael Lechner; Conny Wunsch; Thomas Walter (Institute for the Study of Labor (IZA), 2009)
Many Western economies have reformed their welfare systems with the aim of activating welfare recipients by increasing welfare-to-work programmes and job search enforcement. We evaluate the three most important German welfare-to-work programmes implemented after a major reform in January 2005 (Hartz IV). Our analysis is based on a unique combination of large scale survey and administrative data that is unusually rich with respect to individual, household, agency level, and regional information. We use this richness to allow for a selection-on-observables approach when doing the econometric evaluation. We find that short-term training programmes on average increase their participants' employment perspectives and that all programmes induce further programme participation. We also show that there is considerable effect heterogeneity across different subgroups of participants that could be exploited to improve the allocation of welfare recipients to the specific programmes and thus increase overall programme effectiveness.
urn:nbn:de:101:1-20090330299
Keywords: J68; 330; Welfare-to-work policies; propensity score matching; programme evaluation; panel data; targeting; Aktivierende Sozialhilfe; Hartz-Reform; Arbeitslosenversicherung; Sozialhilfe; Arbeitsmarktpolitik; Wirkungsanalyse; Deutschland